Curriculum Development Models - Dewi, Emillia shandia (Sumatra Journal of Disaster, Geography and Geography Education, 2023)
Abstract The aims of this study were to: 1) find out the meaning of curriculum development models, 2) find out various kinds of curriculum development models, 3) analyze the various advantages and disadvantages of curriculum development models. The method used in this research is research and development in the field of education. Curriculum development cannot be separated from various aspects that influence it, such as ways of thinking, value systems (moral, religious, political, cultural, and social values), the development process, the needs of students, community needs and the direction of education programs. These aspects will be materials that need to be considered in a curriculum development. The curriculum development model is an alternative procedure for designing, implementing, and evaluating a curriculum. Keywords: Curriculum development model, aspects of curriculum development, alternative curriculum development procedures